PENGARUH HARGA, BIAYA PROMOSI, DAN RATA-RATA HARGA PESAING TERHADAP PENJUALAN KAMAR DI APARTEMEN SOMERSET GRAND CITRA JAKARTA - Debora Lasmaria; Bonifasius MH. Nainggolan (LPPM Universitas Asa Indonesia, 2017)
The purpose of this research is to determine the price, promotion costs and average competitors’s price affecting the room sales of Somerset Grand Citra Apartment partially and simultaneously. The population of this research is taken from the profit and loss statement of Somerset Grand Citra for the year of 2011 to 2015. The sample used for this research are the pricing structure, promotion expenses, and competitor’s price list. The sampling technique used for this research is the purposive sampling. Data anlysis tools used for this research are multi linier regression, classic assumption test (normality test, runs test, heteroscedasticity test and multycollinearity test) and the hypothesis test used are the F test, t test, partial correlation analysis and coefficient of determination (